The missional challenge of the HIV/AIDS pandemic for the leadership of the URCSA Kwazakhele Congregation in Port Elizabeth - Kibito, Mziwoxolo Enoch (Stellenbosch : Stellenbosch University, 2011)
Thesis (MTh)--Stellenbosch University, 2011.